Social phobia and self-concept: a correlational study with physical activity practice - Christi Noriko Sonoo; Mirian Lie Hamada; Elton Fernando Hoshino (Universidade Federal de Santa Catarina, 2008)
The objective of this study was to analyze social phobia in teenagers aged 14 to 20 years and its possiblerelationship with regular practice of physical activity and their self-concept. This study enrolled 191 students from privateand public schools and the measurement instruments used were a test of social phobia, a test of self-concept and a physicalactivity questionnaire. The results indicate that students from private schools are shyer than students from public schools. Inrelation to self-concept, there were significant differences in security factor for boys and moral factor for girls. This indicatesthat boys are more stable, brave and secure, while girls are more influenced by moral and ethical rules. These resultsdemonstrate that no relationship was detected between social phobia and physical activity, but it was possible to observea relationship between social phobia and some of the self-concept factors, and a relationship between physical activityand some of the self-concept factors. It is therefore concluded that the negative influence of high levels of social phobia onthe receptivity and security factors of men and women suggests a need for further studies in the area, which could help inthe prevention and treatment of social phobia, which could worsen over the years and compromise these young people'sability to socialize.